Fast Maturation of Splenic Dendritic Cells Upon TBI Is Associated With FLT3/FLT3L Signaling - Zhang, Jin; Li, Zhenghui; Chandrasekar, Akila; Li, Shun; Ludolph, Albert; Boeckers, Tobias Maria; Huber-Lang, Markus; Roselli, Francesco; olde Heuvel, Florian (Frontiers in Immunology, 2022)
The consequences of systemic inflammation are a significant burden after traumatic brain injury (TBI), with almost all organs affected. This response consists of inflammation and concurrent immunosuppression after injury. One of the main immune regulatory organs, the spleen, is highly interactive with the brain. Along this brain–spleen axis, both nerve fibers as well as brain-derived circulating mediators have been shown to interact directly with splenic immune cells. One of the most significant comorbidities in TBI is acute ethanol intoxication (EI), with almost 40% of patients showing a positive blood alcohol level (BAL) upon injury. EI by itself has been shown to reduce proinflammatory mediators dose-dependently and enhance anti-inflammatory mediators in the spleen. However, how the splenic immune modulatory effect reacts to EI in TBI remains unclear. Therefore, we investigated early splenic immune responses after TBI with and without EI, using gene expression screening of cytokines and chemokines and fluorescence staining of thin spleen sections to investigate cellular mechanisms in immune cells. We found a strong FLT3/FLT3L induction 3 h after TBI, which was enhanced by EI. The FLT3L induction resulted in phosphorylation of FLT3 in CD11c+ dendritic cells, which enhanced protein synthesis, maturation process, and the immunity of dendritic cells, shown by pS6, peIF2A, MHC-II, LAMP1, and CD68 by immunostaining and TNF-α expression by in-situ hybridization. In conclusion, these data indicate that TBI induces a fast maturation and immunity of dendritic cells which is associated with FLT3/FLT3L signaling and which is enhanced by EI prior to TBI.